A Molybdenum(0) Isocyanide Analogue of Ru(2, 2′‐Bipyridine)32+: A Strong Reductant for Photoredox Catalysis. Issue 37 (27th July 2016) - Büldt, Laura A.; Guo, Xingwei; Prescimone, Alessandro; Wenger, Oliver S.
Abstract: We report the first homoleptic Mo 0 complex with bidentate isocyanide ligands, which exhibits metal‐to‐ligand charge transfer ( 3 MLCT) luminescence with quantum yields and lifetimes similar to Ru(bpy)3 2+ (bpy=2, 2′‐bipyridine). This Mo 0 complex is a very strong photoreductant, which manifests in its capability to reduce acetophenone with essentially diffusion‐limited kinetics as shown by time‐resolved laser spectroscopy. The application potential of this complex for photoredox catalysis was demonstrated by the rearrangement of an acyl cyclopropane to a 2, 3‐dihydrofuran, which is a reaction that requires a reduction potential so negative that even the well‐known and strongly reducing Ir(2‐phenylpyridine)3 photosensitizer cannot catalyze it. Our study thus provides the proof‐of‐concept for the use of chelating isocyanides to obtain Mo 0 complexes with long‐lived 3 MLCT excited states that are applicable to unusually challenging photoredox chemistry. Abstract : A homoleptic Mo 0 complex with chelating isocyanide ligands was investigated. This chemically robust complex exhibits long‐lived 3 MLCT luminescence, and it is a far stronger photoreductant than d 6 metal diimines made from precious metals. The utility of this complex as a photoredox sensitizer is demonstrated by its successful application in the rearrangement of an acyl cyclopropane to a 2, 3‐dihydrofuran.